Outcrossing and selection of improved guinea pigs from the Cajamarca region to produce superior offspring with high indexes of genetic merit - Mantilla, José (2022)
The study aimed to establish a practice of genetic improvement of guinea pigs based on outcrossing and selection by genetic merit at the Superior Genetics Production Centre (CENPROGEN-SUP), located in the Condebamba valley, Cajamarca region, Peru. The parents of the guinea pigs evaluated came from the inter-Andean valleys of Cajamarca (FICP guinea pigs) and Condebamba (Mangallana guinea pigs and Cholocal guinea pigs). The growth of the offspring of the four crosses was evaluated under the same management and feeding conditions. A total of 80 recently weaned crossbred male guinea pigs (outcross) and selected from the crosses of Mangallana males with pure FICP females (MFp), Mangallana males with crossbred FICP females (MFc), pure FICP males with Cholocal females (FpC) and FICP males crossed with Mangallana females (FcM) were used in the study. In general, the MFp cross obtained the highest average weight at weaning (352.1 g), weight gain (16.7 g/day), body length (36.3 cm) and chest circumference (24.9 cm) at 70 days of age, followed by the MFc cross. There were no differences in feed conversion between groups. It is concluded that outcrossing between superior breeders and the subsequent selection of their offspring for traits of economic importance allows obtaining offspring of genetically superior crossbred males.